Transition-metal-free C-S bond formation: a facile access to aryl sulfones from sodium sulfinates via arynes - Pandya, Virat G.; Mhaske, Santosh B. (Organic Letters, 2014)
Sulfones have been attractive targets for synthetic organic chemists owing to their immense applications in medicinal, material, and synthetic chemistry. In this context, an efficient transition-metal-free process has been demonstrated, wherein a broad range of alkyl/aryl/heteroaryl sodium sulfinates react with varyingly substituted aryne precursors (o-silyl aryl triflates) under mild reaction conditions to afford structurally diverse sulfones in good to excellent yields.